Method for detecting mass ratio of coating metal in copper-steel composite material
The direct dissolution-weighting method detects the metal mass ratio of copper-steel composite coating, which solves the problems of cumbersome detection methods, high safety hazards and low accuracy in the prior art, and achieves a simple operation, safe and environmentally friendly, accurate and reliable detection effect, and is suitable for a variety of copper-based coating materials.
Patent Information
- Application Number
- CN202411634133.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the detection method of metal mass ratio of copper-steel composite material cladding has problems such as cumbersome operation, high safety hazards, insufficient accuracy and limited applicability.
The direct dissolution-weighting method is used to calculate the mass ratio of the cladding metal by heating the copper-steel composite sample in a copper dissolving agent, removing the cladding metal, and then cleaning and drying the steel matrix.
The detection process is simplified, the operation difficulty and detection cycle are reduced, the use of carcinogenic extractants is avoided, the safety and environmental protection of the detection are improved, the accuracy and reliability of the detection results are ensured, and suitable for the detection of various copper-based coating materials.
Smart Images

Figure SMS_6 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of copper-steel composite material detection, and in particular to a method for detecting the mass ratio of coating metal in a copper-steel composite material. Background Art
[0002] Copper-steel composite materials are innovative composite materials based on steel and coated with copper or copper alloys. They are widely used in many fields such as military industry, electronics, currency manufacturing, drinking utensils and architectural decoration. According to specific application requirements, the coating metal can be pure copper, brass, bronze or nickel silver, which enhances the diversity and applicability of the material. However, the performance and production cost of this material are directly affected by the coating metal mass ratio (the ratio of the coating metal mass to the total mass). Therefore, real-time detection and adjustment of the coating metal mass ratio in copper-steel composite materials are crucial.
[0003] At present, the determination of the mass ratio of the coating metal of copper-steel composite materials mainly relies on an indirect determination method, which first determines the mass ratio of copper and zinc in the material separately, and then adds the two ratios. During the operation, the mass ratio of copper is titrated by iodine titration, while the mass ratio of zinc is measured by EDTA titration after extraction with 4-methyl-pentanone-2. However, this method has many problems and limitations.
[0004] Firstly, the operation process of testing the two materials separately is quite cumbersome, which not only increases the difficulty of testing, but also prolongs the testing cycle; secondly, the extractant 4-methyl-pentanone-2 used is a Class 2B carcinogen, which is both flammable and volatile, posing a serious threat to human health and environmental safety; thirdly, as an indirect determination method, its accuracy is affected by multiple sources of error, especially the failure to consider other alloy elements in the copper alloy coating besides copper and zinc, which can easily lead to the results being usually low; and the application scope of this method is limited, and it is mainly suitable for composite materials with coatings of pure copper and ordinary brass, but not for materials with coatings of bronze or white copper. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for detecting the mass ratio of coating metal in copper-steel composite materials, which solves the technical problems of complicated operation process, high safety hazards, insufficient accuracy and limited applicability in the existing indirect determination method for determining the mass ratio of coating metal in copper-steel composite materials. A direct dissolution-weighing method is adopted to simplify the complex step-by-step detection into a single process. The method has the characteristics of simple operation, safety, environmental protection, accuracy and reliability, and is suitable for the detection of various types of copper-based coating materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for detecting the mass ratio of cladding metal in a copper-steel composite material, comprising:
[0008] Sample preparation: The copper-steel composite material is prepared into chips or flakes as test specimens;
[0009] Dissolving the coating: Weigh the prepared sample, put it into a pre-weighed beaker, add the copper solvent solution, stir under water bath heating conditions until the coating is completely dissolved, discard the copper solvent, and obtain the steel substrate;
[0010] Cleaning and separation of steel substrate: clean the steel substrate with new copper solvent, deionized water and anhydrous ethanol in sequence, and dry the cleaned steel substrate together with the beaker;
[0011] Weighing calculation: Weigh the total mass of the dried steel substrate and the beaker, and calculate the coating metal mass ratio based on the mass difference before and after the sample is dissolved.
[0012] As a method for detecting the mass ratio of coating metal in a copper-steel composite material of the present invention, further, the dissolving agent is composed of an oxidant, a complexing agent, a buffer and pure water, and each liter of the dissolving agent contains: 40mL-60mL of hydrogen peroxide, 50g-60g of ammonium persulfate, 60g-80g of disodium ethylenediaminetetraacetate, 400mL-500mL of ammonia water, and 50g-60g of ammonium chloride.
[0013] As a method for detecting the mass ratio of cladding metal in a copper-steel composite material of the present invention, further, the sample preparation includes: preparing a copper-steel composite plate with a thickness greater than 0.50 mm into a chip sample, and shearing a copper-steel composite sheet or strip with a thickness less than or equal to 0.50 mm into a sheet sample.
[0014] As a method for detecting the mass ratio of cladding metal in a copper-steel composite material of the present invention, further, the thickness of the chip sample is less than or equal to 0.20 mm; the size of the sheet sample is less than or equal to 10 mm×10 mm.
[0015] As a method for detecting the mass ratio of cladding metal in a copper-steel composite material of the present invention, further, the weight of the sample is 2g-10g, the volume of the solvent is 250mL-300mL, and the water bath heating temperature is 50°C-60°C.
[0016] As a method for detecting the mass ratio of cladding metal in a copper-steel composite material of the present invention, further, the range of the electronic balance used for weighing is greater than or equal to 220g, and the sensitivity is 0.1mg.
[0017] As a method for detecting the mass ratio of coating metal in a copper-steel composite material of the present invention, further, the calculation formula of the mass ratio of coating metal is: ;
[0018] in, is the cladding metal mass ratio of the copper-steel composite material sample, unit: %
[0019] is the mass of the sample, in g;
[0020] is the mass of the beaker, in g;
[0021] is the total mass of the steel substrate and beaker after drying, in g.
[0022] The beneficial effects of the present invention are:
[0023] The detection method for the mass ratio of coating metal in copper-steel composite material provided by the present invention has significant technical advantages. By adopting the direct dissolution-weighing method, the complex step-by-step detection is simplified into a single process, which not only greatly reduces the difficulty of operation and shortens the detection cycle, but also completely avoids the use of carcinogenic extractants, and significantly improves the operation safety and environmental protection. At the same time, the detection method of the present invention directly determines the total mass of the coating metal without considering the specific composition of each element in the coating, eliminates the cumulative error caused by the indirect determination method, and ensures the accuracy and reliability of the detection result. In addition, the present invention breaks through the limitation that the traditional method is only applicable to pure copper and ordinary brass, and can be widely used in the detection of various copper-based coating materials, including pure copper, brass, bronze and white copper, etc., and the reagents used are all common low-cost inorganic reagents, which has significant economic benefits, and provides a safe, accurate, economical and highly applicable detection scheme for the quality control of copper-steel composite materials. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the present invention clearer and more understandable, the present invention is further described below in conjunction with specific embodiments.
[0025] The invention provides a method for detecting the mass ratio of coating metal in a copper-steel composite material. The core of the method is to remove the copper coating by selective dissolution, weigh the mass of the remaining steel matrix, and thus calculate the mass ratio of the coating metal.
[0026] The specific implementation steps are as follows:
[0027] Sample preparation: The copper-steel composite material to be tested is prepared into chip samples or sheet samples. For plates with a thickness greater than 0.50 mm, prepare them into chip samples with a thickness of less than or equal to 0.20 mm; for thin plates or strips with a thickness of less than or equal to 0.50 mm, cut them into sheet samples with a size of less than or equal to 10 mm × 10 mm.
[0028] Dissolving the coating: Weigh 2g-10g of the prepared sample using an electronic balance with a range greater than or equal to 220g and a sensitivity of 0.1mg, put it into a pre-weighed beaker, and add 250mL-300mL of copper dissolving agent solution; the copper dissolving agent consists of hydrogen peroxide (40mL-60mL / L), ammonium persulfate (50g-60g / L), disodium ethylenediaminetetraacetate (60g-80g / L), ammonia water (400mL-500mL / L) and ammonium chloride (50g-60g / L), and the rest is pure water; place the beaker in a water bath at 50°C-60°C and heat it, and continue stirring until the copper coating is completely dissolved.
[0029] Cleaning and separation of the steel substrate: discard the dissolved solution, and clean the steel substrate with a new copper solvent, deionized water, and anhydrous ethanol in sequence. Each cleaning adopts the pouring method to avoid loss of the steel substrate; put the cleaned steel substrate together with the beaker into an oven and dry it at 90°C-100°C for 10-15 minutes.
[0030] Weighing calculation: Cool the dried steel substrate and the beaker to room temperature and weigh them to an accuracy of 0.0001g; the calculation formula for the coating metal mass ratio is as follows:
[0031]
[0032] in:
[0033] in, is the cladding metal mass ratio of the copper-steel composite material sample, unit: %
[0034] is the mass of the sample, in g;
[0035] is the mass of the beaker, in g;
[0036] is the total mass of the steel substrate and beaker after drying, in g.
[0037] Embodiment 1:
[0038] A copper-steel composite strip is selected, the cladding metal is pure copper T2, the copper content is 99.96%, and the other impurity elements are negligible; the steel matrix is Q195 steel, and the total thickness is 0.20mm. According to the detection method of the present invention, it is first cut into sheet samples with a size controlled within 10mm×10mm, and then the mass is weighed. The flake sample is 5.0032g and placed in a pre-weighed mass Then, add 300mL of copper dissolving agent solution into the beaker, which is prepared by 50mL of hydrogen peroxide, 55g of ammonium persulfate, 70g of disodium ethylenediaminetetraacetate, 450mL of ammonia water, 55g of ammonium chloride and pure water. Then, heat the beaker at 50°C in a water bath, and stir the sample and solution in the beaker until the copper and copper alloy coating are completely dissolved;
[0039] After the dissolution is completed, the solution in the beaker is discarded by pouring method, and it is washed once with new copper solvent solution, twice with deionized water, and twice with anhydrous ethanol to ensure that the copper solvent and impurities on the surface of the steel substrate are thoroughly cleaned. Then, the cleaned beaker and the remaining steel substrate therein are placed in an oven, dried at 90°C for 15 minutes, and cooled to room temperature after being taken out.
[0040] Finally, the beaker and the steel matrix were weighed using an electronic balance to obtain their mass. is 166.8328g, according to the calculation formula of the coating metal mass ratio , calculate the metal mass ratio of the coating layer of the tested sample =12.45%.
[0041] Embodiment 2:
[0042] A copper-steel composite strip is selected, wherein the cladding metal is brass H65, the copper content is 64.10%, the zinc content is 35.82%, and the other impurity elements are negligible; the steel matrix is Q195 steel, and the total thickness is 1.20 mm; according to the detection method of the present invention, firstly, a horizontal milling machine is used to prepare a chip sample with a thickness of about 0.10 mm in the thickness direction, and then the mass is weighed. The crumb sample is 2.5411g and placed in a pre-weighed Then, 250 mL of a copper dissolving agent solution was added to the beaker, and the proportion of the copper dissolving agent was the same as that in Example 1. Subsequently, the beaker was heated at 60° C. in a water bath, and the sample and the solution in the beaker were stirred until the copper and the copper alloy coating were completely dissolved.
[0043] After the dissolution is completed, the solution in the beaker is discarded by pouring, and the steel substrate is cleaned according to the cleaning steps in Example 1. After the cleaning is completed, the beaker and the steel substrate are placed in an oven and dried at 100° C. for 10 minutes, and then taken out and cooled to room temperature;
[0044] Finally, the beaker and the steel substrate were weighed using an electronic balance, and the mass was 160.4802 g. According to the calculation formula of the coating metal mass ratio, , calculate the metal mass ratio of the coating layer of the tested sample =15.49%.
[0045] Embodiment 3:
[0046] In order to verify the applicability of the method of the present invention to the copper-steel composite material whose cladding metal is a non-copper-zinc binary alloy, 0.3000g of iron-nickel copper BFe30-1-1 scrap sample was selected, in which the copper content was 67.44%, the nickel content was 30.45%, the iron content was 0.90%, and the manganese content was 1.18%, and the other impurity elements were negligible; 2.7000g of Q195 steel scrap sample was also selected, and the two scrap samples were mixed as the mass The copper-steel composite material synthetic sample weighs 3.0000g, and the theoretical value of the metal mass ratio of the synthetic sample coating is 10.00%.
[0047] According to the detection method of the present invention, the synthetic sample is first placed in a pre-weighed Then, 280 mL of a copper dissolving agent solution was added to the beaker, and the proportion of the copper dissolving agent was the same as that in Example 1. Subsequently, the beaker was heated at 55° C. in a water bath, and the sample and the solution in the beaker were stirred until the copper and the copper alloy coating were completely dissolved.
[0048] After the dissolution is completed, the steel substrate is treated according to the cleaning and drying steps in Example 1. Finally, the beaker and the steel substrate are weighed using an electronic balance to obtain the mass. is 157.7267g, according to the calculation formula of the coating metal mass ratio , calculate the metal mass ratio of the coating layer of the tested sample =10.03%, which is consistent with the theoretical value, indicating that the method of the present invention has good accuracy for this type of sample.
[0049] Comparative Example 1:
[0050] The copper-steel composite strip sheet sample in which the coating metal used in Example 1 is pure copper T2 was selected. According to GB / T33948.1-2017, the mass ratio of the coating metal copper was measured by iodine titration method to be 12.54%. According to 5.3.3 of GB / T36162-2018, the mass ratio of the coating metal of the test sample was calculated. =12.54%.
[0051] Comparative Example 2
[0052] The shavings of the copper-steel composite strip in which the coating metal used in Example 2 is brass H65 were selected. According to GB / T33948.1-2017, the mass ratio of the coating metal copper was measured by iodine titration to be 9.85%; according to GB / T33948.2-2017, the mass ratio of the coating metal zinc was measured by 4-methyl-pentanone-2 extraction-EDTA titration to be 5.50%. According to 5.3.3 of GB / T36162-2018, the mass ratio of the coating metal of the sample to be tested was calculated. =15.45%.
[0053] Comparative Example 3
[0054] 0.3000g of BFe30-1-1 scrap sample of white copper was selected, and the copper content of the scrap sample was 67.44%, the nickel content was 30.45%, the iron content was 0.90%, and the manganese content was 1.18%, and the other impurity elements were negligible. 2.7000g of Q195 steel scrap sample was also selected. The two scrap samples were mixed as a composite sample of copper-steel composite material with a mass of 3.0000g. At this time, the theoretical value of the metal mass ratio of the composite sample coating was 10.00%. According to GB / T33948.1-2017, the mass ratio of the coating metal copper was measured by iodine titration method: 9.85%; according to GB / T33948.2-2017, the mass ratio of the coating metal zinc was measured by 4-methyl-pentanone-2 extraction-EDTA titration method: <0.10%. According to 5.3.3 of GB / T36162-2018, the metal mass ratio of the coating of the sample to be tested is obtained. =6.76%.
[0055] It can be seen from the test results of Examples 1 and 2 and Comparative Examples 1 and 2 that for the copper-steel composite material whose cladding metal is pure copper and copper-zinc binary alloy, the test results of Examples 1 and 2 are basically consistent with those of Comparative Examples 1 and 2, but the operation procedures of Comparative Examples 1 and 2 are obviously more complicated, and the toxic reagent 4-methyl-pentanone-2 is required in Comparative Example 2. At the same time, the detection cycles of Examples 1 and 2 are both about 1 hour, while the detection cycles of Comparative Examples 1 and 2 are 2 hours and 4 hours, respectively.
[0056] In Example 3, the synthetic sample was measured. For the sample whose coating metal was copper-nickel alloy, the test result was basically consistent with the theoretical value, indicating that the method of the present invention has good accuracy for this type of sample. The test result of Comparative Example 3 was much lower than the theoretical value, indicating that the method used in Comparative Example 3 is not suitable for the determination of materials whose coating metal is elements other than copper and zinc, proving that the present invention has a wider applicability than the method of Comparative Example 3.
Claims
1. A method for detecting the mass ratio of coating metal in a copper-steel composite material, characterized in that: include: Sample preparation: The copper-steel composite material is prepared into chips or flakes as test specimens; Dissolving the coating: Weigh the prepared sample, put it into a pre-weighed beaker, add the copper solvent solution, stir under water bath heating conditions until the coating is completely dissolved, discard the copper solvent, and obtain the steel substrate; Cleaning and separation of steel substrate: clean the steel substrate with new copper solvent, deionized water and anhydrous ethanol in sequence, and dry the cleaned steel substrate together with the beaker; Weighing calculation: Weigh the total mass of the dried steel substrate and the beaker, and calculate the coating metal mass ratio based on the mass difference before and after the sample is dissolved.
2. The method for detecting the mass ratio of coating metal in a copper-steel composite material according to claim 1, characterized in that: The dissolving agent is composed of an oxidant, a complexing agent, a buffer and pure water. Each liter of the dissolving agent contains: 40mL-60mL of hydrogen peroxide, 50g-60g of ammonium persulfate, 60g-80g of disodium ethylenediaminetetraacetate, 400mL-500mL of ammonia water and 50g-60g of ammonium chloride.
3. The method for detecting the mass ratio of coating metal in a copper-steel composite material according to claim 1, characterized in that: The sample preparation includes: preparing a copper-steel composite plate with a thickness greater than 0.50 mm into a chip-like sample, and shearing a copper-steel composite sheet or strip with a thickness less than or equal to 0.50 mm into a sheet-like sample.
4. The method for detecting the mass ratio of coating metal in a copper-steel composite material according to claim 3, characterized in that: The thickness of the chip-like sample is less than or equal to 0.20 mm; the size of the flake-like sample is less than or equal to 10 mm×10 mm.
5. The method for detecting the mass ratio of coating metal in a copper-steel composite material according to claim 1, characterized in that: The weight of the sample is 2g-10g, the volume of the solvent is 250mL-300mL, and the water bath heating temperature is 50°C-60°C.
6. The method according to claim 1, wherein the range of the electronic balance used for weighing is greater than or equal to 220g and the sensitivity is 0.1mg.
7. The detection method according to claim 1, characterized in that: The calculation formula of the coating metal mass ratio is: ; in, is the cladding metal mass ratio of the copper-steel composite material sample, unit: % is the mass of the sample, in g; is the mass of the beaker, in g; is the total mass of the steel substrate and beaker after drying, in g.